DIFFERENCES IN THE NUMBER OF CANDIDA ALBICANS COLONIES ON ACRYLIC RESIN AND THERMOPLASTIC NYLON IN SOURSOP LEAF EXTRACT IMMERSION - Koesoemawati, Ria (Faculty of Dentistry, Mahasaraswati Denpasar University, 2021)
Introduction: Denture stomatitis is a chronic inflammation caused by wearing dentures, mainly caused by Candida albicans. Heat-polymerized acrylic resins are often used as denture bases, but lack the ability to absorb liquids due to their porosity and surface roughness. The basis of the latest dentures is thermoplastic nylon because it is more aesthetically, hypoallergenic and more flexible. Soursop leaf extract contains alkaloids, tannins, flavonoids, and saponins as antifungal. The purpose of this study was to examinate whether there were differences in the number of Candida albicans colonies on heat-polymerized acrylic resin plates and thermoplastic nylon in soursop leaf extract immersion. Materials and Methods: The research design was an experimental pre-post test with control group design, n = 50 plates were divided into 2 groups, heat-polymerized acrylic resin (n=25) and thermoplastic nylon (n=25), divided into 5 groups, 3 treatment groups using 10%,15%,25% soursop leaf extract, Fittident® and aquadest in the control groups. Samples were contaminated with Candida albicans suspension and incubated, counted before immersion for 8 hours, then put in Saboroud’s bath and counted again. Results and Discussions: Wilcoxon test analysis showed significant differences in all groups, except the aquadest group. The Mann-Whitney test showed significant differences between the treatment groups, except between the 25% extract and the Fittident® control group. Also, showed a significant difference in the 15% concentration group between heat-polymerized acrylic resin and thermoplastic nylon. Conclusion: There was a difference in the decrease in the number of Candida albicans colonies on heat-polymerized acrylic resin plates and thermoplastic nylon in soursop leaf extract at a concentration of 15%, while at concentrations of 10% and 25% there was no difference.